PENGARUH PENERAPAN 7 KEBIASAAN ANAK INDONESIA HEBAT TERHADAP PEMBENTUKAN KARAKTER DISIPLIN SISWA SEKOLAH DASAR DI ERA DIGITAL - Riswan; Nur Aisyah Zulkifli (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
The objective of this study is to analyze the implementation of the 7 Habits of Great Indonesian Children in shaping the discipline character of elementary school students in the digital era. These seven habits encompass a range of practices, including early bedtime, early wake-up times, religious observances, physical exercise, consumption of nutritious foods, engagement in educational pursuits, and participation in social activities. This research employs a qualitative case study method conducted in two elementary schools with urban and suburban backgrounds. The data collection techniques employed in this study encompass in-depth interviews, participatory observations, and document analysis. These techniques entail the involvement of informants such as fourth- to sixth-grade students, teachers, and parents. The findings indicate that the implementation of these seven habits contributes positively to fostering student discipline, particularly in aspects of time management, personal responsibility, and academic as well as social discipline. However, significant challenges emerge from the influence of the digital era, including excessive gadget use and distractions from social media, which may impede the efficacy of character-building efforts. The provision of teacher support and the active involvement of parents are identified as crucial factors in addressing these obstacles. This study posits that the 7 Habits of Great Indonesian Children constitutes a pertinent and strategic character development framework to address character education challenges in the digital age, particularly in cultivating student discipline from an early age. This text serves as a significant point of reference for other educational institutions that are endeavoring to establish comprehensive, effective, and sustainable character education systems.